PENGARUH BERBAGAI SKARIFIKASI TERHADAP PERKECAMBAHAN BENIH KEMIRI (Aleurites moluccana Willd.) - Damayanti, Evi; Umar, Husain; Wulandari, Retno; Wahyuni, Dewi; Rahmawati, Rahmawati (Jurnal Warta Rimba, 2021)
Hazelnut (Aleurites mollucana Willd.) is one type of MPTS plant so that hazelnut plants can be used as pioneers in rehabilitation activities. Hazelnuts have a thick seed skin and impermeable or dormant seed properties against water and gas, blocking water imbibisi and oxygen entry into the seeds. Skarification is one of the seed treatment efforts, aimed at breaking dormancy, as well as accelerating the occurrence of uniform seed germination (Sholicha, 2009). There are three types of skarification, namely physical, chemical and mechanical skarification. The treatment of various skarification of hazelnut seeds can increase the germination of hazelnut seeds (Aleurites moluccana Willd.) in real time. This can be seen from the real influence of giving treatment of various skarification to the germination of hazelnut seeds such as the percentage of the number of germinated seeds (G), the average percentage of the number of germinated seeds per day (MDG), the average germination day (GR), and the speed of tumb. Immersion skarification treatment using KNO3 with a consentaration content of 0.2% for 24 hours gives a better influence in the percentage of the number of germinated seeds with an average amount of 44%, the average percentage of germinated seeds per day with an average amount of 0.69%, the average germination day with the number of 42 days, and the speed grows with an average amount of 0.034%/etmal. When compared to other perpetrators.Keywords: Hazelnut, skarification, KNO3, germination